Differentiated E-Module Based on Peer Teaching: Learning Strategy to Increase Student Learning Motivation in Pancasila Education Material - Putu Nado Swastika; I Nengah Suastika; Luh Indrayani; Ketut Sedana Arta (Universitas Pendidikan Ganesha, 2026)
The purpose of this research is to describe the spatial structure and validity of the differentiated E-module based on peer teaching. This research is a research and development (R&D) project using the ADDIE model, with data collected through observation, interviews, and questionnaires. The data in this study were descriptively to describe the design of the differentiated E-module based on peer teaching, and quatitatively used in mto informs regarding the develitsent of the dn the results of the research on the validity of the peer teaching-based differentiated E-module, the results obtained were (1) the evaluation results from two media experts were very well qualified (94% and 95.7%), (2) the evaluation results from Pancasila Education material experts were very well qualified (91.4%), (3) the results of individual trials involving three students were very well qualified overall (95.6%), and (4) the results of small group trials involving eight students were very well qualified overall (94.4%). The results of this study imply that the peer-teaching-based differentiated E-module is highly feasible and has the potential to be used as teaching material in Pancasila Education learning to support increased student learning motivation.